How astronauts use math - Hense, Mary. (New York : Chelsea Clubhouse, 2010)
Looks at some of the many ways in which astronauts use math to walk and eat in space, exercise, land a spacecraft, and perform other industry-related tasks.
Includes bibliographical references (p. 31) and index.
6.8
3-6
3-6
Keywords: Astronautics -- Mathematics -- Juvenile literature; Astronauts -- Juvenile literature; Astronautics -- Mathematics; Astronauts; Astronautics -- Mathematics; Astronauts; Mathematics